2017
DOI: 10.5114/ada.2017.71113
|View full text |Cite
|
Sign up to set email alerts
|

An evaluation of thiol/disulphide homeostasis in patients with psoriasis

Abstract: IntroductionThe role of oxidative stress in the pathogenesis of psoriasis has been investigated in previous studies with conflicting results. On the other hand, well-established treatments currently used in psoriasis exert their effects via a boost of oxidative stress. Recently, a strong positive association between psoriasis, metabolic syndrome and dyslipidemia has also been described showing the complex nature of the disease.AimTo examine thiol/disulphide homeostasis, a newly developed homeostasis assay in p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
9
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 14 publications
(9 citation statements)
references
References 35 publications
0
9
0
Order By: Relevance
“…In the literature, there are few studies performed regarding thiol-disulphide balance in patients with psoriasis. Kilic As a result of this study, lower plasma disulphide levels and higher native thiol levels were detected in patients with psoriasis than healthy individuals [21]. Emre et al performed a study with 90 patients with psoriasis and 76 healthy individuals and examined the homeostasis of thiol/disulphide.…”
Section: Discussionmentioning
confidence: 68%
See 1 more Smart Citation
“…In the literature, there are few studies performed regarding thiol-disulphide balance in patients with psoriasis. Kilic As a result of this study, lower plasma disulphide levels and higher native thiol levels were detected in patients with psoriasis than healthy individuals [21]. Emre et al performed a study with 90 patients with psoriasis and 76 healthy individuals and examined the homeostasis of thiol/disulphide.…”
Section: Discussionmentioning
confidence: 68%
“…Although oxidative stress has been shown to be one of the factors responsible for the pathogenesis of psoriasis in various studies, its role is still unclear. In studies on this subject conflicting results have been reported [14,[19][20][21].…”
Section: Discussionmentioning
confidence: 98%
“…In a study by Aksoy and Kirmit [ 41 ] conducted in a group of 80 psoriasis patients, the results indicated that the thiol–disulphide equilibrium was maintained, but the overall thiol level was lower ( p < 0.01) in psoriasis patients as compared to healthy individuals, whereas the -SS levels revealed no statistically significant differences. In a study by Kilic et al [ 42 ] lower levels of -SS and higher levels of native plasma thiol were reported for psoriasis patients ( n = 92) as compared to healthy subjects, which is indicative of antioxidative imbalance in the organism.…”
Section: The Organism’s Antioxidative Status In Psoriasismentioning
confidence: 99%
“…Recently, TDH has been investigated in various skin disorders [35,36,37]. The parameters that evaluate TDH are native thiol (NT), total thiol (TT), disulfides (DS), and DS/NT, DS/TT, and NT/TT ratios.…”
Section: Introductionmentioning
confidence: 99%